Residues 140–142, 199–200, 222–223, and 262 in the Surface Glycoprotein of Subgroup A Avian Leukosis Virus Are the Key Sites Determining Tva Receptor Binding Affinity and Infectivity - Li, Jinqun; Chen, Jian; Dong, Xinyi; Liang, Canxin; Guo, Yanyan; Chen, Xiang; Huang, Mengyu; Liao, Ming; Cao, Weisheng (Frontiers in Microbiology, 2022)
Subgroup A avian leukosis virus (ALV-A) invades cells through gp85-encoded surface glycoprotein (SU) via specifically recognizing the cellular receptor Tva. To identify the key residues of ALV-A SU that determine the Tva binding affinity and infectivity in DF-1 cells, a strategy of substituting corresponding residues of SU between ALV-A RSA and ALV-E ev-1 (using Tvb as the receptor) was adopted. A series of chimeric soluble gp85 proteins were expressed for coimmunoprecipitation (co-IP) analysis and blocking analysis of viral entry, and various recombinant viruses based on replication-competent avian retrovirus vectors containing Bryan polymerase (RCASBP) were constructed for transfection into DF-1 cells and measurement of the percentage of GFP-positive cells. The results revealed that the substitution of residues V138, W140, Y141, L142, S145, and L154 of host range region 1 (hr1), residues V199, G200, Q202, R222, and R223 of host range region 2 (hr2), and residue G262 of variable region 3 (vr3) reduced the viral infectivity and Tva binding affinity, which was similar to the effects of the -139S, -151N, -155PWVNPF, -201NFD, △214-215 and -266S mutations. Our study indicated that hr1 and hr2 contain the principal receptor interaction determinants, with new identified-vr3 also playing a key role in the receptor binding affinity of ALV-A.